Workshop Implementasi Pembelajaran Berdiferensiasi untuk Forum MGMP Bahasa Indonesia SMA Kabupaten Rokan Hilir - Mukhlis, Muhammad; Shomary, Sudirman; Asnawi, Asnawi; Piliang, Wilda Srihastuty Handayani; Nur, Hidayatun; Yuliawan, Tri; Alber, Alber; Amalia, Rizka; Harum, Ganda (UIR Press, 2026)
This Community Service (PkM) programme aims to improve the competence of senior high school Indonesian language teachers in implementing differentiated learning in response to student diversity and the demands of the Merdeka Curriculum. The activity took the form of a one-day intensive workshop for 26 members of the Indonesian Language MGMP in Rokan Hilir Regency on 25 October 2025. The implementation method included five integrated stages: concept socialisation, training on the principles of differentiation and diagnostic assessment, integration of technology for learning resource curation, practical guidance through simulation, and the formation of a digital learning community. The evaluation results showed a significant improvement in the participants' practical skills, as evidenced by their ability to develop lesson plans (RPP) that integrate variations in content, process, and product, as well as their success in curating digital learning resources relevant to student learning profiles. In addition, a partner satisfaction questionnaire revealed a very high level of success, with 95% of respondents expressing satisfaction with the implementation of the programme. The conclusion from this activity is that practice-oriented workshops supported by sustainable communities are effective in building teachers' capacity to create inclusive learning.